Autism and pervasive developmental disorders - Volkmar, Fred R (Cambridge University Press, 1998)
Featuring contributions from leading authorities in the clinical and social sciences, this volume reflects recent progress in the understanding of autism and related conditions, and offers an international perspective on the present state of the discipline. Chapters cover current approaches to definition and diagnosis; prevalence and planning for service delivery; cognitive, genetic, and neurobiological features; and pathophysiological mechanisms. Interventions reviewed include the pharmacological, behavioral, and educational, and a thoughtful final chapter addresses the nature of the fundamental social disturbance that characterizes autism.
Cambridge monographs in child and adolescent psychiatry
Keywords: pediatrie; psychiatrie